Revisiting Governance Theory: A Comprehensive Framework for 21st-Century Public Administration - Tomi Apra Santosa; Anwar Manahor; Siti Fatimah Bin Salamah (Journal Governance Society, 2025)
The evolving socio-political, economic, and technological landscapes of the 21st century demand a critical reassessment of governance theory to ensure its relevance in addressing complex and dynamic challenges. This study aims to revisit classical and contemporary approaches by examining their strengths, limitations, and applicability to modern public administration. Employing an integrative literature review, the research synthesizes conceptual and empirical insights from governance paradigms including network governance, collaborative governance, and adaptive governance sourced from leading academic databases. The analysis reveals that while classical hierarchical models provide structural stability and clear authority, they are increasingly inadequate for responding to transnational issues such as climate change, pandemics, technological disruption, and global inequality. Conversely, contemporary paradigms highlight the importance of flexibility, stakeholder collaboration, and evidence-based decision-making supported by digital transformation. The findings indicate that effective governance in the 21st century requires an integrated framework that balances normative ideals of transparency, accountability, and inclusivity with practical imperatives of responsiveness, resilience, and innovation. This synthesis underscores the necessity of feedback mechanisms, organizational learning, and multi-level coordination to navigate uncertainty and create sustainable public value. The study concludes that the future of governance lies not in discarding classical theories entirely, but in reconfiguring them through a comprehensive model that harmonizes structural order with adaptability, thus equipping institutions to manage global complexities while preserving legitimacy and public trust.